USING SYSTEM DYNAMICS MODELLING PRINCIPLES TO RESOLVE PROBLEMS OF REWORK IN CONSTRUCTION PROJECTS IN NIGERIA - Olatunji A. AIYETAN; Dillip DAS (Journal of Construction Project Management and Innovation)
Rework in construction projects has brought in two major challenges: cost overruns and delay. In this regards a study was conducted by considering various construction projects in the South West part of Nigeria to understand the causes of rework and the interventions to mitigate it. Survey research methodologies followed by the conceptual system dynamics (SD) modelling were used in the analysis. This study identified the sources of rework in construction projects from the design related, the client related and the contractor related issues and attempted to derive policy/strategic interventions to limit or eliminate rework on construction projects and its delivery by using conceptual SD models based on the influence of the variables on rework. The findings include that inappropriate scheduling for time pressure or delay at the planning stage, lack of adherence to the specifications, and non availability of skilled human resource are the major c auses of rework. However, rework in construction projects would be reduced or eliminated through policy interventions, such as, achieving client satisfaction with scheduling for time pressure or delay at the planning stage, adherence to specifications ensu ring quality of work resulting in client satisfaction, and the availability of skilled manpower ensuring quality management.